Benefits of Zr addition to oxidation resistance of a single-phase (Ni, Pt)Al coating at 1373 K. Issue 7 (July 2019) - Jiang, Chengyang; Qian, Lingyi; Feng, Min; Liu, He; Bao, Zebin; Chen, Minghui; Zhu, Shenglong; Wang, Fuhui
Abstract: A single-phase (Ni, Pt)Al coating with lean addition of Zr was prepared by co-electroplating of Pt-Zr composite plating and subsequent gaseous aluminization treatments. Isothermal and cyclic oxidation behavior of the Zr-doped (Ni, Pt)Al coating samples was assessed at 1373 K in static air in comparison with plain nickel aluminide (NiAl) and normal (Ni, Pt)Al coatings. Results indicated that Zr-doped (Ni, Pt)Al coating demonstrated a lower oxidation rate constant and reduced tendency of oxide scale spallation as well as surface rumpling, in which the enhanced oxidation performance was mainly attributed to the segregation of Zr at oxide scale grain boundaries and the improved Young's modulus of the coating. Besides, the addition of Zr effectively delayed oxide phase transformation of Al2 O3 from θ phase to α phase in the early oxidation stage and coating degradation of β-NiAl to γ'-Ni3 Al in the stable oxidation stage.